Cover Feature: Aggregation‐Induced and Polymorphism‐Dependent Thermally Activated Delayed Fluorescence (TADF) Characteristics of an Oligothiophene: Applications in Time‐Dependent Live Cell Multicolour Imaging (Chem. Asian J. 24/2019). Issue 24 (26th November 2019) - Sarkar, Samir Kumar; Pegu, Meenakshi; Behera, Santosh Kumar; Narra, Siva Krishna; Thilagar, Pakkirisamy
Abstract : A donor‐acceptor (D‐A) architecture‐free oligothiophene‐based molecular system was developed that showed conformational controlled aggregation induced emission (AIE) and polymorph selective thermally activated delayed fluorescence (TADF) via spin‐orbit coupling. The aggregate emission covered a broad wavelength range, which showed multicolor (green, yellow and red) imaging in the living cells with longer emission lifetime of up to 8 μs. More information can be found in the Communication by Pakkirisamy Thilagar et al. on page 4588 in Issue 24, 2019 (DOI: 10.1002/asia.201901138 ).